Pengaruh In-group favoritism terhadap Perilaku Diskriminasi Pada Karyawan Etnis Tionghoa Di Makassar - Muhrajan Piara; Muhammad Nur Hidayat Nurdin; Kurniati Zainuddin; Khairunnisa Putri Abrar (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
The purpose of this study is to measure the influence of in-group favoritism towards discrimination on the workplace, especially between Indonesian employees and Chinese workers. In-group favoritism of an individual will affect the discrimination in an organization. This study was conducted in Makassar, South Sulawesi. The participants of this study were 34 which consisted of 15 male and 19 female and came from private sector. This study used self-report to measure participants’ tendency towards two variables. In-group favoritism was measured by adaptation scale from (Luhtanen & Crocker, 1992), while discrimination variable used Lewis’ scale. Data analysis used regression model with SPSS 25 for Windows. The significance of hypothesis showed p = 0.35, which indicated the non significant result. The result of this study showed that in-group favoritism has no influence towards discrimination to Chinese workers.